Analysis of the impact of climate change on the woody plants vegetation in the Botanical Garden of the Ukrainian National Forestry University - Nelia Lukianchuk; Levko Bliusyuk; Nadia Bliusyuk; Nataliіa Kendzora; Liliіa Koliada (Наукові праці Лісівничої академії наук України)
Climatic changes have a significant impact on the growth and development of ornamental plants in the urban environment, the climatic conditions of the territory have a great impact on the ecological state of plants and determine their ability to adapt and develop in a certain region. When assessing the adaptive capacity of plants, the introduction of phenological observations has found wide application, providing a more in-depth study of the biological characteristics and ecological properties of plant organisms. The purpose of our paper was to study the influence of weather and climate changes on the timing of the phenophase of the growing season of ornamental woody plants. To analyze climate changes, average monthly quantitative indicators of air temperature and precipitation were calculated using archive data from the Lviv airport meteorological station.